Are scientists perceived as credible experts? - Anders Broström; Cornelia Lawson; Mabel Sanchez Barrioluengo (The University of Manchester, The Manchester Institute of Innovation Research (MIoIR), 2024)
Science is widely embraced as an important prerequisite for innovation, and there is widespread support for public investment in science on that basis. It remains less clear to what extent the general public also perceives science as a relevant source of expertise on technological development and innovation. Drawing on representative panels from two European countries (the United Kingdom and Sweden), we investigate whether scientists are perceived as credible senders of messages regarding future technological development and its consequences. We apply a conjoint analysis methodology. Specifically, we estimate the credibility of scientists by comparing how respondents' assessments of societal challenges statements change with the attribution of that statement to scientists, compared with attribution to other type of expert groups (government, businesspersons, and issue advocates). While our study identifies positively framed predictions about new technology and innovation as a domain where scientific expertise is perceived as enjoying relatively high credibility, actors representing business and special interest groups are overall perceived as more credible conveyors of `bad news', of negatively framed messages about the future. Implications for our understanding of the social contract of science are discussed.
Keywords: 330; Scientific Experts; Expertise; Trust in Science; SDGs; Emerging Technologies